Growth mechanisms from tetrahedral seeds to multiply twinned Au nanoparticles revealed by atomistic simulations. Issue 8 (20th June 2022) - El koraychy, El yakout; Roncaglia, Cesare; Nelli, Diana; Cerbelaud, Manuella; Ferrando, Riccardo
Abstract : Atomic level simulations supported by density-functional theory calculations identify the key mechanisms of the twinning process in gold tetrahedral nanoparticles, which is shown to originate from the growth kinetics of the pure, ligand-free metal. Abstract : The growth pathways from tetrahedral to multiply twinned gold nanoparticles in the gas phase are studied by molecular dynamics simulations supported by density functional theory calculations. Our results show that the growth from a tetrahedron to a multiple twin can take place by different pathways: directly from a tetrahedron to a decahedron (Th → Dh pathway), directly from a tetrahedron to an icosahedral fragment (Th → Ih), and from a tetrahedron to an icosahedron passing through an intermediate decahedron (Th → Dh → Ih). The simulations allow to determine the key atomic-level growth mechanism at the origin of twinning in metal nanoparticles. This mechanism is common to all these pathways and starts from the preferential nucleation of faulted atomic islands in the vicinity of facet edges, leading to the formation and stabilization of twin planes and of fivefold symmetry axes.